Effect of 2014 massive flood on well water qualities: a case study on Kelantan River basin, Malaysia - Ab. Rahman, Hariz Azhar; Ibrahim, Noor Azlina; Abdul Hamid, Azzmer Azzar; Tengku Abdul Hamid, Tengku Haziyamin (Institute of Technology and Life Sciences in Falenty, 2018)
The effect of physical and biological qualities of wells after submergence was assessed following December 2014 flood in Kelantan. Studies were carried out on a total of 65 wells from 13 stations around Kelantan River basin in which the wells’ water were sampled for pH, total dissolved solid (TDS), turbidity and microbial contamination. About 95% of the well showed to be contaminated, 7 out of 65 samples (11.1%) showed TDS values >400 μSꞏcm–1; and 19 samples (29.2%) recorded turbidity beyond 7.0 NTU. Statistical non-parametric tests carried out on independent groups showed that the status of well contamination was neither determined by both degree of submergence nor by the geographical location. Also the physico-chemical parameters are independent of flood inundation. However, TDS and turbidity values changed based on geographical location, at p < 0.05. Well from estuary recorded higher TDS (241.2 μSꞏcm–1 ±159.5 SD) and turbidity (8.04 NTU ± 6.53 SD) compared to those from inner basin (TDS at 156.3 μSꞏcm–1± 88.9 SD; turbidity at 2.90 NTU ± 2.46 SD), respectively. The flood water had played significant role in the transmission of existing contaminant, and most of the wells were unsafe for drinking. We concluded that the degree of flood submergence does not necessarily determine the severity of the well contamination